The effectiveness of cognitive-behavioral training of emotional regulation on marital happiness and cognitive emotional regulation of women with symptoms of premenstrual dysphoric disorder (PMDD) - Nouhi, Shahnaz; Naseryfadafan, Malake; Salehian, Roza; Saghari, Samira (International Journal of Applied Behavioral Sciences, 2021)
Background and Aim:Premenstrual dysphoric disorder (PMDD) is a new DSM-5 diagnosis characterized by the cyclical emergence of emotional and physical symptoms in the luteal phase of the menstrual cycle. The present study aimed to evaluate the effectiveness of cognitive-behavioral training of emotional regulation on marital contentment and cognitive emotional regulation of women with signs of premenstrual dysphoric disorder (PMDD). Materials and Methods:The method of this research is semi-experimental by pre-test/post-test with experimental and control groups. The statistical population consisted of all women suffering from premenstrual dysphoric disorder referring to the clinic of the BaharHospital in Shahrood. A total of 30 women which were selected through purposive sampling among women whose scores in pre-menstrual symptoms screening questionnaire were higher than the mean, and were replaced in the experimental and control groups (15 women for each group). Then, both groups completed the Marital Happiness Questionnaire and the Cognitive Emotional Regulation Questionnaire and then the experimental group underwent cognitive-behavioral emotion regulation training in form of 90-minutes, 12 sessions once a week. After completion of training, both groups again completed the above questionnaires. Data were analyzed using SPSS software version 24 and one and multivariate analysis of covariance (MANCOVA). Results:The results showed that cognitive-behavioral training of emotion regulation has a significant effect on marital happiness and cognitive emotion regulation (P<0.05). Conclusion:It can be concluded that Cognitive behavioral emotion regulation training can increase cognitive emotion regulation and marital happiness in women with symptoms of premenstrual dysphoric disorder